Study on thickening mechanism of thickened acid carbonate acidizing fracturing thickener based on SEM - Mak, Yu Quan (Nanyang Technological University, 2024)
Polyacrylamide is a polymer gel that is commonly used as a thickener in acid fracturing to enhance oil recovery from carbonate reservoirs. They undergo thermal degradation when exposed to high temperate conditions, reducing viscosity and fracturing effectiveness. The network structure of polyacrylamide, composed of pores and branches, changes with thermal degradation. Despite visual evidence from scanning electron microscopy, quantifying these changes and correlating it to viscosity reduction requires further research. This study involves quantifying the spatial network structure parameters consisting of pore area, perimeter, width and branch width using an image analysis software, ImageJ. The SEM image consisting of network structures at six controlled temperatures was analysed in this study. Insights to the correlation of these parameters to viscosity of polyacrylamide is generated through graphical analysis of statistical measures and frequency distribution diagrams. The study revealed that for 120°C, 135°C and 150°C, the average pore size increases by 1.3%, 59.8% and 160.7% from the initial average at the base temperature of 20°C, showing that pore size negatively correlates with viscosity. On the other hand, the branch width shows a unique, fluctuating relationship with viscosity for these four temperatures. This observation is associated with the increase in pore size as well as the formation of a coalesced gel structure at certain temperatures, which correlates to viscosity reduction. It was also discovered that high variability in pore size and branch width corresponds with low viscosity. These findings suggests that if network parameters can be regulated, the viscosity can be controlled. This could pave the way for future developments in the construction of polyacrylamide.